Critical role of smoking and household dampness during childhood for adult phlegm and cough: a research example from a prospective cohort study in Great Britain. Issue 4 (19th April 2014) - Cable, Noriko; Kelly, Yvonne; Bartley, Mel; Sato, Yuki; Sacker, Amanda
Abstract : Objective: To examine independent associations between childhood exposures to smoking and household dampness, and phlegm and cough in adulthood. Design: A prospective cohort study. Participants: 7320 of the British cohort who were born during 1 week in 1970 and had complete data for childhood and adult information. Main outcome measures: Experiences of phlegm and coughing over the previous 3 months were assessed using questions from the Medical Research Council (MRC) Questionnaire on respiratory symptoms when the cohort participants were 29 years of age. 4 response patterns (no symptoms, phlegm only, cough only, both symptoms present) were created based on the responses to these questions. Results: Childhood smoking and exposure to marked household dampness at age 10 were associated with phlegm (childhood smoking: relative risk ratio (RRR)=1.45, 95% CI 1.02 to 2.05; dampness: RRR=2.05, 95% CI 1.07 to 3.91) and co-occurring cough and phlegm (childhood smoking: RRR=1.35. 95% CI 1.08 to 1.67; dampness: RRR=2.73, 95% CI 1.88 to 3.99), while exposure to two or more adult smokers in the household was associated with cough-related symptoms (cough only: RRR=1.28, 95% CI 1.04 to 1.58; phlegm and cough: RRR=1.32, 95% CI 1.06 to 1.64). These associations were independent from adult smoking, childhood phlegm and cough, early social background and sex. Current smoking at age 29 contributed to all symptom patterns; however, a substantial association between household dampness and co-occurring phlegm and cough suggest long-term detrimental effects of childhood environmental exposures. Conclusions: Our findings give support to current public health interventions for adult smoking and raise concerns about the long-term effects of a damp home environment on the respiratory health of children.